2008
DOI: 10.1056/nejmoa0804915
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Combination Antimalarial Therapies in Children from Papua New Guinea

Abstract: The most effective regimens were artemether-lumefantrine against P. falciparum and dihydroartemisinin-piperaquine against P. vivax. The relatively high rate of treatment failure with dihydroartemisinin-piperaquine against P. falciparum may reflect cross-resistance between chloroquine and piperaquine. (Australian New Zealand Clinical Trials Registry number, ACTRN12605000550606.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
214
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(238 citation statements)
references
References 32 publications
19
214
5
Order By: Relevance
“…In a study conducted in Thailand 21 comparing the efficacy of CQ and AL combined with a 14-day course of primaquine, full treatment success was achieved in the CQ treatment group, whereas the treatment success with AL was slightly lower at 97.4%. Another study also reported greater post-treatment prophylaxis in averting P. vivax recurrences with dihydroartemisinin-piperaquine than with AL, 22 and dihydroartemisin-piperaquine has been indicated as highly efficacious as AL for the treatment of P. vivax . 23 …”
Section: Discussionmentioning
confidence: 95%
“…In a study conducted in Thailand 21 comparing the efficacy of CQ and AL combined with a 14-day course of primaquine, full treatment success was achieved in the CQ treatment group, whereas the treatment success with AL was slightly lower at 97.4%. Another study also reported greater post-treatment prophylaxis in averting P. vivax recurrences with dihydroartemisinin-piperaquine than with AL, 22 and dihydroartemisin-piperaquine has been indicated as highly efficacious as AL for the treatment of P. vivax . 23 …”
Section: Discussionmentioning
confidence: 95%
“…[10][11][12][13] Reappearance of parasitemia after drug treatment can result from either (1) recrudescence of surviving asexual bloodstage parasites, (2) relapse from dormant liver stages known as hypnozoites, or (3) new infections with unrelated parasites. Molecular genotyping of paired parasite samples usually makes a distinction between recrudescences (with the same genotype as the initial infection) and new infections (with a different genotype), but relapses may originate from reactivation of either the same parasite clone found in the primary bloodstream infection (homologous hypnozoites) or another, genetically different clone (heterologous hypnozoites).…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of this treatment regimen was found to be low only 3 years after its implementation, 2 which gives a strong argument for the introduction of artemisinin-based combination therapies. A recent study conducted in PNG 3 has tested the efficacy of different artemisinin-combination therapies in children < 5 years of age with Plasmodium falciparum or Plasmodium vivax malaria. Artemether-lumefantrine was found to be the most effective combination therapy against P. falciparum with an adequate clinical and parasitological response of 97.3% at Day 28 and 95.2% at Day 42 after treatment.…”
Section: Introductionmentioning
confidence: 99%